The research field of science communication. Studies of public opinion, scientists and scientific institutions. - Entradas, M. (LSE MPhil/LSE Seminar Series, 2019)
Entradas et al. (2019). What are research institutions doing across countries and what are their drives for public communication? 29 January 2019, LSE MPhil/LSE Seminar Series, London, UK, Invited presentation.